2014
DOI: 10.5539/ijbm.v10n1p14
|View full text |Cite
|
Sign up to set email alerts
|

S&P/TSX 300 Companies’ Political Connections, Compliance with Board of Directors Regulations and Financial Performance

Abstract: Corporate governance best practices, especially when not mandated, usually mitigate risk and provide value added (Agrawal & Knober, 1996). Many authors have demonstrated a link between corporate governance and institutional and regulatory environments (Claessens & Yurtoglu, 2012;LaPorta, Lopez-de-Silanes, Shleifer & Vishny 1998;Liu, 2006;Matoussi & Jardak, 2012) and even political power (Claessens & Yurtoglu, 2012). Political connections are known to result in numerous privileges for firms, such as decreased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 44 publications
(25 reference statements)
1
19
0
1
Order By: Relevance
“…ROA, ROE and solvency were negatively influenced by political connections. These results partially confirmed our hypothesis and partially supported previous findings related to companies in other industries, which have shown that political connections have a positive effect on financial performance (Dicko & Breton, 2013a;Dicko & El Ibrami, 2013;Dicko & Khemakhem, 2015). …”
Section: Conclusion and Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…ROA, ROE and solvency were negatively influenced by political connections. These results partially confirmed our hypothesis and partially supported previous findings related to companies in other industries, which have shown that political connections have a positive effect on financial performance (Dicko & Breton, 2013a;Dicko & El Ibrami, 2013;Dicko & Khemakhem, 2015). …”
Section: Conclusion and Discussionsupporting
confidence: 82%
“…8, No. 11;2016 In Canada, Dicko, and Breton (2013a) and Dicko and Khemakhem (2015) showed that politically connected Canadian companies performed better financially than non-politically connected companies. Their performance was measured using return on assets and return on equity ratios.…”
Section: The Effect Of Political Connections On Companies Other Than mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Canadian context, Dicko and Khemakhem (2015) showed that politically connected S&P/TSX firms performed better financially (measured by return on assets and return on equity) than non-politically connected firms. Dinc (2005) investigated the influence of politics on government-owned banks in 43 countries (excluding the United States), finding that, relative to private banks, these banks increased their lending in election years.…”
Section: Political Connections and Firms' Financial Performancementioning
confidence: 99%
“…Since certain regulations in the US (e.g. on corporate governance) are more stringent than in Canada, Canadian companies behave differently when listed on US financial markets (Khemakhem & Dicko, 2013;Dicko & Khemakhem, 2015). We therefore decided to include this variable in our study, using a dummy variable valued at 1 if the company is listed on US markets and 0 otherwise.…”
Section: Control Variablesmentioning
confidence: 99%